AURORA: bariatric surgery registration in women of reproductive age - a multicenter prospective cohort study. Issue 1 (December 2016) - Jans, Goele; Matthys, Christophe; Bel, Sarah; Ameye, Lieveke; Lannoo, Matthias; Van der Schueren, Bart; Dillemans, Bruno; Lemmens, Luc; Saey, Jean-Pierre; van Nieuwenhove, Yves; Grandjean, Pascale; De Becker, Ben; et al.
Abstract Background The expansion of the obesity epidemic is accompanied with an increase in bariatric procedures, in particular in women of reproductive age. The weight loss induced by the surgery is believed to reverse the negative impact of overweight and obesity on female reproduction, however, research is limited to in particular retrospective cohort studies and a growing number of small case-series and case-(control) studies. Methods/design AURORA is a multicenter prospective cohort study. The main objective is to collect long-term data on reproductive outcomes before and after bariatric surgery and in a subsequent pregnancy. Women aged 18–45 years are invited to participate at 4 possible inclusion moments: 1) before surgery, 2) after surgery, 3) before 15 weeks of pregnancy and 4) in the immediate postpartum period (day 3–4). Depending on the time of inclusion, data are collected before surgery (T1), 3 weeks and 3, 6, 12 or x months after surgery (T2-T5) and during the first, second and third trimester of pregnancy (T6-T8), at delivery (T9) and 6 weeks and 6 months after delivery (T10-T11). Online questionnaires are send on the different measuring moments. Data are collected on contraception, menstrual cycle, sexuality, intention of becoming pregnant, diet, physical activity, lifestyle, psycho-social characteristics and dietary supplement intake. Fasting blood samples determine levels of vitamin A, D, E, K, B-1, B-12 and folate, albumin, total protein, coagulation parameters, magnesium, calcium, zinc and glucose. Participants are weighted every measuring moment. Fetal ultrasounds and pregnancy course and complications are reported every trimester of pregnancy. Breastfeeding is recorded and breast milk composition in the postpartum period is studied. Discussion AURORA is a multicenter prospective cohort study extensively monitoring women before undergoing bariatric surgery until a subsequent pregnancy and postpartum period. Trial registration Retrospectively registered (July 2015 -NCT02515214 )